PENGARUH KECERDASAN EMOSIONAL TERHADAP KEPEMIMPINAN DAN ORGANISASI - Lies Indriyatni (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
Emotional Intelligence reflects on how a knowledge will be applied and developed in a person’s life. A great leader is someone, who has a good Emotional intelligence and understand very well on how them personality will influences people in his organization.Emotional Intelligence has a great influens on someone’s leadership since an effective leadership is a leadership that has 4 emotional intelligence element’s. Those elements are :Self – awareness; Self – Management; Social – awareness; Relationship management Besides that, emotional intelligence also play role on the organization, because the organization where each members has a good emotional intelligence, will be able to work well and has a high productivity.